2022
DOI: 10.5603/mrj.a2022.0037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the associations between GDF-15, OPG, and IL-15 levels in CRC: preliminary results

Abstract: Introduction: Osteoprotegerin (OPG), , and Growth/Differentiation are all proven to take part in the processes associated with colorectal carcinoma (CRC) including tissue remodeling, inflammation modulation, and metastasis.Aim of the study: To investigate the concentrations of GDF-15, OPG and IL-15 in tumor and margin tissues of CRC in relation to clinicopathological features of patients. Material and methods:The study used 50 specimens of tumor and tumor-free margin tissues obtained from CRC patients. To det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…54,55 These results are perfectly in line with the valuable potential of GDF-15 for CRC detection and prognosis. 14,17,20,21,22,47,[56][57][58][59][60] Indeed, it has been reported that GDF-15 levels in serum gradually increase in the process of conversion from adenomatous polyps to colorectal carcinoma 14,59 and that CRC patients with an increased serum level of GDF-15 had a 2.09-fold higher risk of death 11 and worse cancer-specific survival (CSS). 21 In our results, this would correspond to the CRC plasma samples at advanced stages (1.85-fold higher GDF-15 plasma values than healthy individuals).…”
Section: Analysis Of Plasma Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…54,55 These results are perfectly in line with the valuable potential of GDF-15 for CRC detection and prognosis. 14,17,20,21,22,47,[56][57][58][59][60] Indeed, it has been reported that GDF-15 levels in serum gradually increase in the process of conversion from adenomatous polyps to colorectal carcinoma 14,59 and that CRC patients with an increased serum level of GDF-15 had a 2.09-fold higher risk of death 11 and worse cancer-specific survival (CSS). 21 In our results, this would correspond to the CRC plasma samples at advanced stages (1.85-fold higher GDF-15 plasma values than healthy individuals).…”
Section: Analysis Of Plasma Samplesmentioning
confidence: 99%
“…19,20 Therefore, GDF-15 dysregulation within the SASP framework underlines its relevance as a well-established biomarker for detecting and characterizing metastatic CRC. 15,21,22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation